THE EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES THROUGH RME APPROACH TO MATHEMATICS SUBTRACTION OPERATION IN 4TH GRADE SDN SUKASARI 2 - Rasmita, Rasmita; Hodijah, Hodijah (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractThe consequences that can be generated from conventional learning methods are lectures are too dominant, as if the teacher is the only resource person who is versatile, student learning outcomes in mathematics are very low, and the average score is very low. The mathematics score of 4th grade is only 55 while the Minimum Completeness Criteria is 65. With those problems, teachers need to try to increase the learning motivation, so the students learning scores can increase above the predetermined MCC score. One of the efforts that teachers can do is to try to apply the learning strategies by applying interactive learning models. This research uses 2 rounds of classroom action research, and each round consists of four phases, namely; planning, acting and observing, reflecting, and considering. The subjects of this research were 4th grade students of SD Negeri Sukasari 2 and the data used were the daily test scores. The average score of the pre-cycle was 55.48, the first cycle was 69.68, and the second cycle was 87.10.Keywords: Student Learning Outcomes; Realistic Mathematics Education